A Screening Strategy for Metal Antitumor Agents as Exemplified by Gold(III) Complexes. Issue 4 (1999) - Fricker Fricker, Simon P. Simon P.
Abstract : The use of a screening strategy based on human tumor cell lines, which are also tumorigenic in immune-deprived mice, is described. Activity against the human tumor cells in vitro and in vivo, is complemented with studies on the mechanism of action. This aporoach is demonstrated using 2-[(dimethylamino)-methyl]phenyl (damp) gold(III) compounds of the type [Au X2(damp)], where X = chloride, thiocyanate, acetate, or the bidentate ligands oxalate and malonate. All compounds were shown to be selectively active against a human bladder tumor cell line (HT1376) in vitro, and active in an in vitro panel of ovarian tumor cell lines. The acetato complex was shown to be active in experimental animal models of both the HT1376 bladder tumor, and the CH1 ovarian tumor. Although the [AuX2(damp)] compounds share structural features in common with cisplatin, and exhibit interesting in vivo activity against human tumor cells, the data indicate that they have a very different biochemical mechanism from platinum-based drugs and represent a potentially new class of metal-based antitumor agents.